P01.04 APEX-mediated biotinylation as a potent tool for evaluation of chemokine-receptor interactions and respective binding inhibitors. (21st September 2022) - Beimert, A; Perleberg, C; Meyer, B; Kühnemuth, B; Schnell, K; Layritz, P; Grün, J; Gärtig, J; Piseddu, I; Bahner, K; Endres, S; Anz, D
Abstract : Background: The immunosuppressive tumor microenvironment (TME), which is strongly shaped by regulatory T cells (Treg), represents a major drawback for anti-cancer immunity and cancer immunotherapy. The migration of Treg into the TME is mediated by the CC chemokine receptor 4 (CCR4) whose main ligand, CCL22, is overexpressed in many tumor entities and is associated with unfavorable prognosis. Therefore, therapeutic blockade of the CCR4-CCL22 axis to suppress Treg migration is a promising strategy to overcome tumor-derived immune suppression. To study such chemokine-receptor interactions and to assess the binding capacity of potential inhibitors, we aimed to establish a screening tool using APEX-mediated biotinylation. Materials and Methods: In the presence of hydrogen peroxide, the enzyme ascorbate peroxidase (APEX) oxidates biotin-phenol to short-lived, highly reactive radicals that biotinylate structures in close proximity. Using a streptavidin-linked fluorophore that strongly binds biotin, the biotinylated structures can subsequently be analyzed and quantified via flow cytometry. To analyze the binding capacity of inhibitors of the CCR4-CCL22 axis, a CCL22-APEX fusion protein was created that binds to CCR4-expressing cells. Thus, the level of biotinylated CCR4 + cells reflects on the receptor-ligand interaction. A strongly reduced biotinylation of CCR4 + cells upon addition of an inhibitor indicates an effective inhibitory binding capacity. Results: In vitro binding assays using APEX proximity labeling were established to create a testing platform for inhibitors of the CCR4-CCL22 axis. For analysis of the murine and human system, CCR4-overexpressing B3Z cells and CCRF-CEM cells that endogenously express CCR4 were used, respectively. In both settings, a strong biotinylation was achieved by adding the CCL22-APEX fusion protein as compared to only APEX as a control for unspecific biotinylation. Addition of two different CCR4 antagonists, C-021 and AZD-2098, lead to significant and dose-dependent reduction of target cell biotinylation. The same assay was conducted using CCR4-transduced primary murine T cells, showing equivalent results. Further, we could demonstrate a decreased biotinylation of cells when recombinant CCL22 had been added, indicating competitive binding inhibition. Conclusion: This work reveals a novel application of the APEX proximity labeling system to identify new chemokine-receptor interactions and to screen inhibitors for their binding capacity, facilitating further evaluation of promising inhibitors in functional experiments in vitro and in vivo . The adaption of the assay protocol for suspension cells and not only adherent cell lines also allows the use of primary murine as well as human cells. Overall, our results present a valuable tool for the evaluation of novel inhibitors of chemokine-receptor axes for immunotherapy of malignant diseases. Disclosure Information: A. Beimert: None. C. Perleberg: None. B. Meyer: None. B. Kühnemuth: None. K. Schnell: None. P. Layritz: None. J. Grün: None. J. Gärtig: None. I. Piseddu: None. K. Bahner: None. S. Endres: None. D. Anz: None.